"The goddess of the room": Birth as a feminist issue among doulas and mothers. (September 2020) - Henley, Megan M.
Abstract: This article focuses on how feminism informs women's birth choices in the U.S. Through twenty-five interviews with doulas (labor support people) and twenty-five interviews with mothers, I look at how feminism affects these women's views and approaches to birth. I found that birth is a feminist issue to most. Both groups described feminism in terms of "empowerment, " and saw doula support as a good way to regain power lost in the patriarchal system of medicine. Most interviewees took a neoliberal feminist approach to systemic issues, whereby participants championed hiring a private service (doula support) to supplement impersonal maternal health care. At this point, doula support remains restricted to women who can access it and afford it. The findings from this study suggest that feminism leads women to challenge male-centered obstetric medicine and seek out individual solutions (like hiring doulas) to systemic issues of patriarchy in contemporary maternity care.